2016
DOI: 10.1111/bjd.14713
|View full text |Cite
|
Sign up to set email alerts
|

Dual c-JunN-terminal kinase-cyclin D1 and extracellular signal-related kinase-c-Jun disjunction in human melanoma

Abstract: Dual disjunction between JNK-cyclin D1 and ERK-c-Jun signalling forms the basis for further investigation of combined JNK and MAPK signalling blockade as a more effective therapeutic approach in human melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
19
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 49 publications
1
19
1
Order By: Relevance
“…S3 in Pathria et al .) . Therefore, while the pharmacological results appear to contradict, the genetic results support Lopez‐Bergami et al .…”
mentioning
confidence: 57%
See 3 more Smart Citations
“…S3 in Pathria et al .) . Therefore, while the pharmacological results appear to contradict, the genetic results support Lopez‐Bergami et al .…”
mentioning
confidence: 57%
“…Using two different JNK inhibitors in a panel of melanoma cell lines they show that JNK signalling is required for proliferation and survival of melanoma, independent of the mutational status . Pharmacological JNK inhibition mitigated c‐JUN activity and expression but failed to suppress cyclin D1 levels both at the protein and transcript levels and, consequently, to induce G 1 arrest . However, silencing c‐JUN by small interfering RNA (siRNA) decreased cyclin D1 levels (see Supplementary Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the c‐Jun N ‐terminal kinase (JNK) signalling cascade, which is important for tumour cell proliferation, has been implicated in resistance of melanoma to MAPK inhibition. Building upon this finding, a study by Pathria et al demonstrated that combination treatment of BRAF mutant melanoma with MAPK kinase (MEK) and JNK inhibitors significantly inhibited proliferation compared with single‐agent treatment, indicating that targeting of multiple prosurvival signalling pathways may be necessary to overcome acquired resistance to BRAF/MEK inhibition …”
mentioning
confidence: 99%